Implementasi Penomoran Hunian dalam Upaya Standarisasi Tata Ruang Lingkungan di 6 Jorong Nagari Sungai Rumbai Timur - Jurnil Ardi; Ahmad Zikron Irfani; Silvia Fitri Rahmadani; Sisca Vitriani; Vera Melinda S; Wero Oktaviandra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to analyze the implementation of residential numbering as an effort to standardize environmental spatial planning in six hamlets of Nagari Sungai Rumbai Timur and to examine its contribution to improving the effectiveness of population administration services. This research employed a qualitative approach using a descriptive method. The study was conducted in six hamlets, namely Pasa Pagi, Bukit Berbunga, Balai Timur, Kambang Baru, Kampung Baru, and Ujung Koto. Data collection techniques included observation, interviews, and documentation. The findings revealed that before the implementation of residential numbering, the population administration system in Nagari Sungai Rumbai Timur had not operated optimally due to the uneven distribution of house numbers and the absence of a clear and structured numbering system. This condition caused difficulties in locating residents’ houses, conducting population data collection, distributing social assistance, and providing administrative services. The implementation of residential numbering had a positive impact on environmental spatial organization and the effectiveness of public services. With a more structured and uniform house numbering system, population data collection became easier, house addresses could be identified more quickly, and the environment appeared more organized and orderly. This study indicates that residential numbering plays an important role in supporting environmental standardization and improving the quality of population administration at the village level.